2019
DOI: 10.1259/bjr.20190389
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for precision education in radiology

Abstract: In the era of personalized medicine, the emphasis of health care is shifting from populations to individuals. Artificial intelligence (AI) is capable of learning without explicit instruction and has emerging applications in medicine, particularly radiology. Whereas much attention has focused on teaching radiology trainees about AI, here our goal is to instead focus on how AI might be developed to better teach radiology trainees. While the idea of using AI to improve education is not new, the application of AI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 64 publications
2
66
0
2
Order By: Relevance
“…A number of resources have emerged attempting to specifically address this concern for radiology professionals taught to varying levels of ability. 10 , 11 , 12 , 13 , 14 , 15 , 16 While these resources are tailored to imaging applications, as of writing we have found few examples of formal integration into residency training.…”
Section: Introductionmentioning
confidence: 99%
“…A number of resources have emerged attempting to specifically address this concern for radiology professionals taught to varying levels of ability. 10 , 11 , 12 , 13 , 14 , 15 , 16 While these resources are tailored to imaging applications, as of writing we have found few examples of formal integration into residency training.…”
Section: Introductionmentioning
confidence: 99%
“…The postlearning score in the AIL group was significantly better than the prelearning score. Thus, the AI-based education system demonstrated its utility in improving trainee performance through quality measures that should be integral to the improvement in medical education, especially with the utilization of AI [7,17,18]. Furthermore, we found that the HipGuide system particularly helped novice students who had lower prelearning scores.…”
Section: Discussionmentioning
confidence: 75%
“…In conventional image teaching, students are expected to first learn diagnostic characteristics from educators and practice afterward. AI in medical education is still in the development stage [2,7,[24][25][26]. AI can empower flipped classroom-like teaching [27,28] and complete the existing bottom-up platforms used to teach radiology [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For segmentation and rendering of anatomic details of interest, many different software solutions are available to fit specific requirements or personal preferences. Recent research in 3D segmentation and rendering focuses on automation, e.g., using artificial intelligence [9]. However, to produce anatomically precise and reproducible models of a patient's individual anatomy, it is still important to confirm correct results in every step of the 3D printing process, i.e., to implement quality control mechanisms, which requires expertise of specialized personnel [23].…”
Section: Introductionmentioning
confidence: 99%